PENCIPTAAN KARYA CETAK TINGGI DENGAN MIXED MEDIA SEBAGAI UPAYA MENCIPTAKAN INOVASI DAN KREASI BERBASIS TRADISI JAWA - Adi, Sigit Purnomo; Pandanwangi, Ariesa; Marutama, I Gusti Ngurah Tri; Yudhanto, Sigied Himawan (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2021)
Relief print is one of the techniques in graphic arts. The process of making a relief print is considered easy because it uses simple tools and materials, so that the artwork produced from this relief printing process is considered less creative and innovative. Conventional printmaking rules have predefined indicators. This creation research aims to produce novelty in graphic arts based on the concept of Javanese tradition. The method used is a mix of methods, namely the artistic creation process method: experimentation, reflection and creation of works. The creation of high-level printed artworks is made with a mix of media on the basis of Javanese tradition visually, so it is hoped that these works of art will be able to compete in the international world. The results of this creation research have innovations and creations in the form of contemporary art works extracted from Javanese traditional art.